INITIAL TRAINING OF MATHEMATICS TEACHERS: RELEVANT ASPECTS FOR A REFLECTIVE PRACTICE - Mirele Alves Medeiros, Maria; Willames Cirino Oliveira, Wesley (Revista Gênero e Interdisciplinaridade, 2024)
This study portrays the importance of initial training for mathematics teachers with aspects of praxis, with reflective practice as a relevant factor in the teaching/learning process. It is necessary to integrate specific and pedagogical knowledge with mathematical content, valuing the diversity of knowledge, contributing to the student’s critical stance. The aim is to emphasize that initial training needs to be ongoing, developing skills related to how to mediate knowledge for students, as well as understanding the specific knowledge of the subject taught. Training focused on praxis, as discussed throughout this work, allows educators to review their teaching methodologies and strategies with a view to student learning. It is essential that this preparation be consistent with the practice experienced in educational institutions, that is, future educators must be aware of the reality they will experience when they take over a classroom while still in their undergraduate studies. Therefore, significant initial training should guide students to constantly reflect on educational praxis.